Water Quality Suitability and Sanitary Inspection of Hand-Dug Wells of Merawi Town, Ethiopia - Selamawit Tadele; Andinet Kebede Tekile (Ethiopian Journal of Science and Sustainable Development)
In small towns of developing countries, because of unreliable piped water supply, households utilize water from private shallow wells, which can be easily contaminated. In this study, water quality suitability of hand-dug wells, which are the main alternative to the utility water provision in Merawi Town, and the risk of the sources to contamination were assessed. Samples from 14 wells were analyzed for 12 selected water quality parameters, and the overall water quality was judged using Weight Arithmetic Water Quality Index (WAWQI). Besides, sanitation practices of the town residents were evaluated through questionnaires administered to 386 householders and sanitary inspections of the sources were conducted using the World Health Organization form. Based on the results, temperature, electrical conductivity, total dissolved solids, chloride, nitrate, and magnesium were within the acceptable limit of drinking. However, all the water samples were bacteriologically contaminated. According to the WAWQI, only 14.29% of the samples waters were good for domestic use in both wet and dry seasons. From the sanitary inspection, 71.43% of the wells were at either high or very high risk of contamination; however, from the responses to the questionnaire, 57.3% of households do not treat the alternative sources. To overcome the bacteriological contamination and thus, the outbreak of diseases, short-term intervention, such as ensuring disinfection is compulsory. To achieve, the missing access to potable water, the utility needs to develop long-term goals. Generally, water quality analysis and sanitary inspection are complementary tools, which play the important purposes of ensuring water safety.